Ottoline goes to school - Riddell, Chris (Harper, 2009)
Ottoline and Mr. Munroe, her very helpful dog, enroll in the Alice B. Smith School for the Differently Gifted and while Ottoline worries that she may not have a special gift, Mr. Munro worries about the ghost that is said to haunt the school at night.